Three wood isotopic reference materials for [delta]2H and [delta]13C measurements of plant methoxy groups - Greule, Markus; Moossen, Heiko; Lloyd, Max K.; Geilmann, Heike; Brand, Willi A.; Eiler, John M.; Qi, Haiping; Keppler, Frank (Chemical geology, 2020)
Methoxy groups (OCH3) of plants show specific stable carbon and hydrogen isotope patterns that are used for applications in biogeochemical, atmospheric, paleoclimatic and food research. The method of choice for determining stable hydrogen and carbon isotope values of methoxy groups (δ2HOCH3 and δ13COCH3 values) is the conversion to gaseous iodomethane (CH3I) and subsequent measurement by stable isotope ratio mass spectrometry. However, comparative measurements particularly for stable hydrogen isotopes of plant methoxy groups are limited due to the lack of suitable reference materials. We have prepared three batches of powdered wood samples (birch HUBG3, beech HUBG4, and tineo HUBG5) collected from different geographical locations to serve as long-term reference materials for normalization of δ2HOCH3 but also δ13COCH3 values. Methoxy contents of the three wood samples range between 4.7 and 5.4%. Methoxy groups from subsamples of the three homogenized wood samples were quantitatively converted to CH3I and δ2HOCH3 and δ13COCH3 values of this CH3I were calibrated against international reference substances by high-temperature conversion- and elemental analyzer isotope ratio mass spectrometry. The δ2HOCH and δ13COCH3 values of HUBG3 and HUBG4 at 1σ uncertainty calibrated to the VSMOW and VPDB isotopic δ-scale, respectively are −272.9 ± 1.5 mUr and −29.40 ± 0.13 mUr; and −239.1 ± 1.4 mUr and −30.17 ± 0.13 mUr, respectively. In addition, the calibrated δ2HOCH value of HUBG5 is −191.7 ± 0.8 mUr. Whilst the δ2HOCH3 values of the three wood samples span a relatively wide range (~−280 to −190 mUr) suitable for normalization of δ2HOCH3 values of most plant samples that have been reported so far, δ13COCH3 values are restricted to a composition (~−30 mUr) typical of wood methoxy groups. We suggest that the three investigated wood materials HUBG3-5 are ideally suited for long-term usage, inter-laboratory comparison, and together with the two recently reported methyl sulfate salts (HUBG1 and HUBG2) complete a new set of solid methoxy reference materials that cover almost the full range of plant methoxy groups reported so far. Therefore, we recommend replacing liquid CH3I and instead use the solid reference materials set HUBG1-5 for normalizing δ2HOCH3 and δ13COCH3 values to the respective δ-scales.
Available online 25 November 2019
Im Titel sind die Zahlen "2" und "13" im Titel hochgestellt
Im Titel ist delta als griechischer Buchstabe dargestellt
Gesehen am 30.03.2020